2023
DOI: 10.3390/land12071272
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Identification Methods of Urban–Rural Integration Zones from the Perspective of Symbiosis Theory and Urban Expansion Theory

Abstract: Urban–rural integration zones are areas with the most prominent and complex contradictions in economic and social, humanistic and geographical, and urban–rural contexts. Properly identifying such zones is essential for promoting urban–rural integrated development and rural revitalization efforts. In this study, symbiosis theory and urban expansion theory are employed to analyze and identify the spatial characteristics of urban–rural integration zones in the main urban area of Dalian City. Two distinct methods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…They concluded that the free flow of factors between urban and rural areas is crucial for rural development, and it is an effective way to crack the pattern of unbalanced urban-rural development [38]. The essence of urban-rural symbiosis lies in achieving the equitable sharing of social development benefits between urban and rural areas [39]. These studies provide theoretical guidance for enhancing urban-rural symbiosis, emphasizing that the removal of institutional and mechanistic barriers to the flow of factors between urban and rural areas, as well as the promotion of free flow and equitable exchange of factors, are crucial for advancing the level of urban-rural symbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the free flow of factors between urban and rural areas is crucial for rural development, and it is an effective way to crack the pattern of unbalanced urban-rural development [38]. The essence of urban-rural symbiosis lies in achieving the equitable sharing of social development benefits between urban and rural areas [39]. These studies provide theoretical guidance for enhancing urban-rural symbiosis, emphasizing that the removal of institutional and mechanistic barriers to the flow of factors between urban and rural areas, as well as the promotion of free flow and equitable exchange of factors, are crucial for advancing the level of urban-rural symbiosis.…”
Section: Introductionmentioning
confidence: 99%